Yttrium-90 therapy and 99MTc pertechnetate knee uptake measurements in the management of rheumatoid arthritis. Issue 2 (April 1983) - Kyle, V; Hazleman, B L; Wraight, E P
Abstract : Twenty-eight knees with chronic arthritis and effusion were treated with intra-articular 90Y. Synovial activity was assessed by measuring 99mTc pertechnetate uptake. There was a significant difference in uptake between controls and patients. Those who had a good response to 90Y (15 patients) showed a significant decrease in uptake, not seen in those who failed to respond. The pattern of 90Y distribution was examined and appeared to correspond to areas of increased synovial activity; these patterns and their significance have not been previously reported. Factors which could help to predict response to 90Y are discussed.